The Role of Leverage as A Mediating Influence Between Profitability and Firm Size on Firm Value - Herda; Tubagus Ismail; Wulan Retnowati (Indonesian Journal of Economic & Management Sciences, 2024)
This research is conducted to investigate the influence of Profitability and Firm Size on Firm Value using Leverage as a variable of mediating. This research employs a quantitative approach and secondary data. The population consists of industrial sector companies listed on the Indonesia Stock Exchange Index Classification (BEI-IC) during the 2018-2022 period, with a sample selected using purposive random sampling, totaling 110 companies. The data is analyzed using multiple linear regression analysis The outcomes of this research are (1) Profitability gives a significant effect on Leverage. (2) Firm Size leaves out a significant effect on Leverage. (3) Profitability constructs a significant effect on Firm Value. (4) Firm Size does not have a significant effect on Firm Value. (5) Leverage has a significant effect on Firm Value. (6) Leverage works as a mediating variable between the significant influence of profitability on firm value. (7) Leverage as a mediating variable between the significant influence of firm size on firm value